A Qualitative Multi-Theoretic Analysis of Boyz N The Hood (1991): Exploring The Cinematographic Representation of Crime and Racism (Social Science Review, 2025)
This paper examines the experiences of Bangladeshi female garment workers regarding patriarchy, empowerment, and emotional well-being. While some authors have argued that paid work in the garment sector has improved women’s status and liberated them from patriarchal restrictions, others emphasized the double burden of work and household chores and the experiences of violence both in the family and at the workplace. This article argues that while garment work has improved garment workers’ economic conditions, they experience anxiety and diminished emotional well-being due to separation from children. Furthermore, this article also argues that while paid employment in the RMG sector has enhanced women’s consumption capacity, women still adhere to patriarchal ideologies by relinquishing their income to their husbands and not owning assets in their names. Understanding economic empowerment in relation to patriarchy and emotional well-being is crucial for holistically assessing garment workers’ experiences.Social Science Review, Vol. 42(1), June 2025, pp. 79-99